Study on Physico-Chemical Parameters of Wastewater Effluents from Cotton Development Plant of Maroua-Cameroon - Abba Paltahe; Tsamo Cornelius; Abdoul Wahabou (The Journal of Pure and Applied Chemistry Research, 2018)
The present research work deals with the study of some of the important physico-chemical parameters of wastewater effluents collected from Maroua cotton processing plant named “SODECOTON”. The effluents were studied from the month of June 2016 to August 2017. A preliminary investigation was carried out on the source of water used by the plant and management of its wastewater effluent. All parameter were analyzed as per the standard methods. Water quality parameters such as temperature, pH, Electrical Conductivity, Total Dissolved Solid, Total Suspended Solid, Biological Oxygen Demand, Chemical Oxygen Demand, Total Nitrogen Kjeldahl, Nitrate and Phosphate were analysed. Results of this study shows that nearly all values of these parameters were above permissible limit. These values are significantly higher during the rainy season (from May –December) than dry season (January-April). Water used by the plant is from bore hole. This water is treated by less adapted technology prior to use and thus probably contribute in the pollution load of the plant’s wastewater effluent. Wastewater from the plant is discharged without being treated and without any quality analysis. This behaviour is due to very relax regulation, absence of monitoring and enforcement by government authorities.